2021
DOI: 10.1007/s10266-021-00608-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laser modalities on shear bond strengths of composite superstructure to zirconia and PEEK infrastructures: an in vitro study

Abstract: In the last decade, demand for metal-free esthetic restorations has grown considerably due to the development of materials to fulfill the need for an esthetic prosthesis. We examined the effects of erbium-doped yttrium aluminum garnet (Er:YAG), neodymium-doped yttrium aluminum garnet (Nd:YAG), and potassium titanyl phosphate (KTP) laser applications on the shear bond strength (SBS) of nanohybrid composite superstructures to zirconia and PEEK infrastructures. Zirconia and PEEK specimens were prepared with CAD/C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…8.09 MPa. Hence, this work indicated that Nd:YAG laser treatment was the most effective method [207]. Another study reported that CO 2 and Er:YAG lasers increased the shear bond strength of PEEK to veneering resin from ca.…”
Section: Laser Treatmentmentioning
confidence: 71%
“…8.09 MPa. Hence, this work indicated that Nd:YAG laser treatment was the most effective method [207]. Another study reported that CO 2 and Er:YAG lasers increased the shear bond strength of PEEK to veneering resin from ca.…”
Section: Laser Treatmentmentioning
confidence: 71%
“…The current study used ALC for PEEK surface treatment, resulting in improved bond strength between PEEK and resin, effectively refuting the null hypothesis. Tsuka et al [ 30 ] and Shabib et al [ 31 ] reported a SBS range of 13.2–16.3 MPa for PEEK surfaces treated with an Nd:YVO 4 laser, and Ulgey et al [ 34 ] achieved SBS values of 16.4 MPa and 11.3 Mpa when treating PEEK surfaces with Nd:YAG and KTP lasers, combined with a nanohybrid composite, respectively. In the current study, ALC-treated PEEK surfaces exhibited an SBS with resin cement ranging from 5.62 to 8.01 MPa before artificial aging ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have used lasers, including CO 2 [ 29 ], neodymium-doped yttrium aluminum garnet (Nd:YAG) [ 30 , 31 ], erbium-doped yttrium aluminum garnet (Er:YAG) [ 32 ], erbium, chromium:yttrium-scandium-gallium-garnet [ 33 ], and potassium titanyl phosphate (KTP) [ 34 ], to irradiate dental materials, resulting in improved bond strength. However, the widespread adoption of computer numerical control (CNC) lasers in dental clinical practice is hindered by limitations such as device size and laser source intensity.…”
Section: Introductionmentioning
confidence: 99%
“…However, the potential of the combination of Er:YAG laser with sandblasting (SBS, 12.09 ± 2.08 MPa) or silica-modified sandblasting (SBS, 13.14 ± 1.45 MPa) to improve the adhesion performance of PEEK should not be overlooked [103]. Elsewhere, Nd:YAG laser resulted in the highest SBS (16.35 ± 0.63 MPa), followed by Er:YAG laser (14.29 ± 0.49 MPa) and then KTP laser (11.3 ± 0.41 MPa); all had significant effect in improving adhesion (Untreated PEEK, 8.09 ± 0.55 MPa), and PEEK exhibited better bonding performance than zirconia after laser treatment [104]. Nd:YVO 4 laser groove treatment can enhance the SBS not only between PEEK and veneering composite resin, but also between PEEK and various resin-based luting agents, and the improvement of SBS is directly related to the depth of penetration of the Nd:YVO 4 laser (200-µm, 15.0 ± 5.3 MPa > 150-µm, 14.4 ± 4.8 MPa > 100-µm, 13.2 ± 5.4 MPa > Untreated, 4.5 ± 2.9 MPa) [80].…”
Section: Laser Treatmentmentioning
confidence: 96%
“…This indicates that additional effort should be dedicated to determining the best combination of luting cements and pretreatment methods for improved the bonding performance of PEEK. Few of the surface modification methods that are currently available for PEEK exhibit the safety and operability required for regular clinical practice [84,91,97,104], and much of the available research so far has concentrated on fixed dental restoration, with the bonding behavior of PEEK examined only in vitro or via FEA. More effort should be dedicated to clinical trials in order to fully assess the long-term performance.…”
Section: Future Perspectivementioning
confidence: 99%